Inovasi Pengembangan Bahan Ajar PAI Berbasis Teknologi Digital Untuk Pembelajaran Daring - Nazwa Siti Aisyah; Muhamad Zaki Rido Ginanjar; Windani; Fiqra Nazib (Yayasan Al-Afif, 2024)
Innovation in the development of educational materials based on digital technology is crucial, especially in the context of increasingly challenging daring learning. The purpose of this study is to investigate various methods and effects of using digital learning materials in the era of Industry 4.0. The method used is a systematic literature review (SLR), which analyzes 25 pertinent articles. The results indicate that multimedia applications such as video, animation, and interactive writing can improve students' understanding of PAI material. However, there are still certain drawbacks, such as the slowness of digital infrastructure and the lack of teacher proficiency while using technology. This study suggests that in order to achieve effective education, there needs to be a shift toward digital learning materials that are engaging and relevant to students' needs.